Occurrence of banana bunchy top virus in tissue-cultured and conventional banana cultivars in the Siang region of Arunachal Pradesh, India - Singh, Raghuveer; Banerjee, Amrita (Indian Journal of Plant Protection, 2026)
Short Communication